Clinical outcomes, MRI evaluation and predictive factors of indirect decompression with lateral transpsoas approach for lumbar interbody fusion: a multicenter experience - Petrone, Salvatore; Ajello, Marco; Marengo, Nicola; Bozzaro, Marco; Pesaresi, Alessandro; Allevi, Mario; Fiumefreddo, Alessandro; Denegri, Federica; Cogoni, Maurizio; Garnero, Andrea; Tartara, Fulvio; Di Perna, Giuseppe; et al. (Frontiers in Surgery, 2023)
Introduction: Evaluating the effects of indirect decompression obtained through lateral lumbar interbody fusion (LLIF) by clinical improvements and radiological parameters on MRI scans. Identifying predictors of better decompression and clinical outcome. Materials and methods: From 2016 to 2019, patients who underwent single- or double-level indirect decompression LLIF were consecutively reviewed. Radiological signs of indirect decompression were evaluated in preoperative and follow-up MRI studies and were subsequently correlated to clinical data, expressed as axial/radicular pain (VAS back/leg), index of disability (Oswestry Disability Index) and clinical severity of lumbar stenosis (Swiss Spinal Stenosis Questionnaire). Results: 72 patients were enrolled. The mean follow-up was 24 months. Differences in vertebral canal area (p<0.001), height of the foramina (p<0.001), thickness of the yellow ligament (p=0.001) and anterior height of the interbody space (p=0.02) were observed. Older age (p=0.042), presence of spondylolisthesis (p=0.042), presence of intra-articular facet effusion (p=0.003) and posterior height of the implanted cage (p=0.020) positively affected the increase of the canal area. Change in root canal area (p<0.001), height of the implanted cage (p=0.020) and younger age (p=0.035) were predictive factors of root pain relief, while increased vertebral canal area (p=0.020) and height of the interbody fusion cage (p=0.023) positively affected the severity of clinical stenosis. Conclusions: LLIF indirect decompression showed both clinical and radiological improvements. Presence and degree of spondylolisthesis, presence of intra-articular facet effusion, age of the patient and height of the cage were predictive factors of major clinical improvements.